The Role of Perceived Social Support on Self-Regulated Learning of High School Students at Islamic Boarding Schools - Agistni Sarah Sakinah; Tamanna Quraishi; Tang Eng Loong (Education Specialist, 2025)
Education plays a fundamental role in improving the quality of life. It enables individuals to develop themselves intellectually, socially, and morally. In the context of Islamic boarding schools, education not only focuses on the acquisition of knowledge and skills, but also emphasizes the cultivation of values, ethics, and religious commitment. The goal is to shape Muslim individuals who are faithful, pious, possess good character, contribute positively to society, and uphold the values of Islam. One key factor that influences students’ learning behavior is perceived social support. This study aims to examine the role of perceived social support in fostering self-regulated learning among high school students in Islamic boarding schools. This research adopts a quantitative approach using correlational methods to assess the relationship between variables. Data were collected through the distribution of a transadapted perceived social support scale among high school students enrolled in Islamic boarding schools. The results revealed a statistically significant relationship, with a p-value of 0.000 (p < 0.05), a correlation coefficient (R) of 0.430, and a coefficient of determination (R²) of 0.185. This indicates that perceived social support contributes 18.5% to students’ self-regulated learning. Further analysis of sub-scales showed the following contributions: teachers (11.1%), friends (9.5%), people at school (9.2%), classmates (8.9%), and parents (6.1%). In conclusion, perceived social support plays a significant role in enhancing students’ self-regulated learning in Islamic boarding schools. These findings underscore the importance of fostering supportive environments, especially from educators and peers, to improve students' independent learning capabilities.